Evidence of ultrafast dissociation in the CHCl3 molecule. (8th December 2020) - Santos, A C F; Vasconcelos, D N; MacDonald, M A; Sant'Anna, M M; Tenório, B N C; Rocha, A B; Morcelle, V; Bonfim, V S; Appathurai, N; Zuin, L
Abstract: In the present work, we use tunable synchrotron radiation to investigate experimentally and theoretically the dissociation of a chlorinated methane, the CHCl3  molecule, by exciting a chlorine 2 p core electron into the LUMO and LUMO + 1 orbitals. The Auger electron energy distribution measured at the Cl 2p3/2 → 10a1 resonance shows narrow lines which energies correspond to the Cl * → Cl + atomic decay, a clear evidence that the Auger decay takes place after consummation of the dissociation, when the moieties were already far away from each other. Our experimental data are endorsed theoretically by a series of high-level ab initio quantum mechanical calculations. The excited states are calculated to be strongly repulsive in the Franck–Condon region (−d E /d y ∼ 0.15 a.u.) along the C–Cl bond direction.